Implementasi Program Koperasi Konsumen Ekonomi Syariah Roda Dua untuk Meningkatkan Kesejahteraan Masyarakat dalam Berwirausaha - Ramadhan, Adrian; Frinaldi, Aldri (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
This study aims to examine the implementation of the Sharia Economic Consumer Cooperative (Kokesra) Roda Dua program by the West Sumatra Province Cooperative and MSME Office in improving community welfare through entrepreneurship, as well as identifying the obstacles faced. The method used is descriptive qualitative, with interviews and documentation studies as data collection techniques, and source triangulation as a method to verify data validity. The results showed that the West Sumatra Cooperative and MSME Agency has implemented the Kokesra program to empower MSMEs in Padang City through several steps. First, providing business capital using a profit-sharing system to MSMEs. Second, implementing savings and loan services managed by cooperative employees. However, in its implementation, there are a number of obstacles. Among others, not all MSMEs are eligible for loans, many businesses do not have official permits, and the limited budget available for the Kokesra program. This research provides an overview of the efforts that the local government has made in encouraging sharia entrepreneurship, but also highlights the challenges that need to be overcome to ensure the sustainability and effectiveness of the program in improving overall community welfare.